Russia-Ukraine war and the global crisis: Impacts on poverty and food security in developing countries - Arndt, Channing; Diao, Xinshen; Dorosh, Paul A.; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2022)
Global food, fuel, and fertilizer prices have risen rapidly in recent months, driven in large part by the fallout from the ongoing war in Ukraine and the sanctions imposed on Russia. Other factors, such as export bans in response to concerns about commodity shortages, have also contributed to rising prices. Figure 1 examines price changes in key food and nonfood commodities between June 2021 and June 2022. The period of interest for this study is June 2021 to April 2022. Over this period, palm oil and wheat prices increased by 68 and 113 percent in nominal terms, respectively. When deflated by the US Consumer Price Index, these price changes equate to 56 and 100 percent in real terms. Wide variation exists across food products, with nominal maize prices increasing by 19 per-cent (or 11 percent in real terms), and rice prices declining by 13 percent (or 7 percent in real terms) over the same period. Prices of nonfood commodities also rose substantially. Whereas crude oil prices rose 44 percent (or 34 percent in real terms), natural gas and fertilizer prices both doubled (or 88 and 101 percent in real terms, respectively). As shown in the breakdown in the bar chart, most of the price growth occurred after the start of the war in Ukraine, except for fertilizer.